Stres akademik dengan intensitas perilaku merokok mahasiswa yang sedang menyusun skripsi - Aswad, La Ode Afdal; Siregar, Nani Restati; Sunarjo, ida Sriwati (Jurusan Psikologi FKIP Universitas Halu Oleo, 2024)
Smoking intensity is the state, extent, or amount of activity of a person who burns or smokes tobacco, and the potential for smoke inhalation by those around them. The purpose of this study was to clarify the relationship between academic stress and the intensity of students' smoking behavior during thesis writing. The population in this study was his 73 and the sampling used the total sampling method, namely 73 people. The instruments used in this study were the 23-item Academic Stress Scale and the 27-item Smoking Behavioral Intensity Scale. Based on the results of the product moment correlation test, the significance value for the two variables is less than 0.005, or 0.000. On the other hand, the results of Pearson's correlation test showed a value of 0.113 for both variables. The test results show a positive correlation between the academic stress variable (X) and the smoking behavior intensity variable (Y).